BIOÉTICA Y FORMACIÓN PARA LA BIOLOGÍA EN EL SIGLO XXI - Linares Márquez, Pascual (Acta Biológica Colombiana, 2024)
Biology as a scientific discipline faces epistemological and bioethical challenges, which arise at the dawn of the 21st century. This discipline must address problems such as the loss of biological diversity and vocational training, generate strategies to face this situation and integrate bioethics to establish new forms of relationship between humans and other life forms. Also, generating technology to modify biological systems, including molecular biology and complex genetics, requires new ethics from possible artificial modifications, especially for biomedical purposes. Bioethics is a discipline that was born in the seventies of the last century and has the mission to accompany scientific knowledge by analyzing bioethical dilemmas that emerge from the intervention of living beings, to ensure the preservation and integrity of living systems as free and autonomous entities. This paper addresses the changes in biology from its beginnings to date, the circumstances it has faced from various epistemologies, and the attention to the challenges within the discipline to generate relevance with global requirements. There is a need to integrate bioethics into the training of biologists, from the establishment of committees for research ethics and bioethics committees, as well as informed consent, in the processes of applying science, For the survival of all living systems, human and non-human.